The good fairy [videorecording (DVD)] - Wyler, William, 1902-1981; Sullavan, Margaret, 1909-1960; Marshall, Herbert, 1890-1966; Morgan, Frank, 1890-1949; Molnár, Ferenc, 1878-1952 (Kino on Video, 2002)
Young Louisa Ginglebusher is recruited from a local orphanage to become an usherette at a movie theater. Encouraged by her kindly guardian to spread her wings, Louisa decides to lead the life of a fairy tale angel & in her quest to do good she tries to redirect money from a rich playboy to a struggling lawyer.